2006
DOI: 10.1128/jvi.80.2.634-642.2006
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of Cell Cycle Control in T Cells Contribute to the Different Outcomes of Simian Immunodeficiency Virus Infection in Rhesus Macaques and Sooty Mangabeys

Abstract: In contrast to human immunodeficiency virus (HIV) infection of humans and experimental simian immunodeficiency virus (SIV) infection of rhesus macaques (RMs), SIV infection of sooty mangabeys (SMs), a natural host African monkey species, is typically nonpathogenic and associated with preservation of CD4+ T-cell counts despite chronic high levels of viral replication. In previous studies, we have shown that the lack of SIV disease progression in SMs is related to lower levels of immune activation and bystander … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
(78 reference statements)
1
22
0
Order By: Relevance
“…Therefore, it is conceivable that these B cell subsets are partially responsible for the hypergammaglobulinemia observed during chronic SIV infection in RhMs. The lack of hypergammaglobulinemia and the restoration of total and memory B cell subsets, in addition to the well-described resolution of immune activation in AGMs during the early stages of SIV infection (65)(66)(67), support the notion that natural hosts lack the B cell dysfunction that likely impairs antibody responses during pathogenic SIV infection. We also identified several differences in the B cell populations and immunoglobulin content in milk of SIV-infected AGMs and RhMs.…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, it is conceivable that these B cell subsets are partially responsible for the hypergammaglobulinemia observed during chronic SIV infection in RhMs. The lack of hypergammaglobulinemia and the restoration of total and memory B cell subsets, in addition to the well-described resolution of immune activation in AGMs during the early stages of SIV infection (65)(66)(67), support the notion that natural hosts lack the B cell dysfunction that likely impairs antibody responses during pathogenic SIV infection. We also identified several differences in the B cell populations and immunoglobulin content in milk of SIV-infected AGMs and RhMs.…”
Section: Discussionmentioning
confidence: 63%
“…The most intriguing feature of naturally SIVinfected SMs is that, unlike HIV/SIV-infected humans and RMs, these animals typically remain asymptomatic and do not progress to AIDS despite levels of plasma viremia that are as high, or even higher, than those observed in HIV-infected patients (14,15). Although the mechanism(s) underlying the lack of disease progression in SMs is still unknown, our previous studies have shown that a characteristic feature of this infection is the overall preservation of peripheral blood (PB) CD4 ϩ T cell homeostasis that occurs in the absence of the chronic immune activation, bystander T cell apoptosis, and cell cycle dysregulation that are associated with pathogenic primate lentiviral infections (15)(16)(17)(18)(19).…”
mentioning
confidence: 76%
“…Based on a series of previous studies conducted in relatively small cohorts of naturally and experimentally SIV-infected SMs, we proposed that attenuated immune activation may be instrumental in maintaining the AIDS-free state of these animals (11,17,28). From an evolutionary perspective, these studies suggested that SMs (and perhaps other natural hosts for SIV) have adapted to the selective pressure of SIV infection and have reached a disease-free equilibrium that does not require strict control of viral replication (with viral loads that are as high if not higher than those seen during pathogenic HIV infection) but instead results from a general attenuation of the overall level of immune activation.…”
Section: Discussionmentioning
confidence: 99%